Diseño de un sistema primario en el proceso de trituración de llantas usadas desalambradas (2016)
Design and modeling performed by finite element software of a primary system in the shredding process of used wireless car tires from rim 13 inches to rim 19 inches is made, pieces of about 5 to about 7 cm are obtained with this system. This project aims to recover the major components of discarded tires, reducing the environmental damage that this generals.